QoS-Aware Radio Access Technology (RAT) Selection in Hybrid Vehicular Networks - Hameed Mir, Zeeshan; Toutouh-el-Alamin, Jamal; Fethi, Filali; Alba-Torres, Enrique (Springer, 2015)
The increasing number of wireless communication technologies and standards bring immense opportunities and challenges to provide seamless connectivity in Hybrid Vehicular Networks (HVNs). HVNs could not only enhance existing applications but could also spur an array of new services. However, due to sheer number of use cases and applications with diverse and stringent QoS performance requirements it is very critical to efficiently decide on which radio access technology (RAT) to select. In this paper a QoS-aware RAT selection algorithm is proposed for HVN. The proposed algorithm switches between IEEE 802.11p based ad hoc network and LTE cellular network by considering network load and application’s QoS requirements. The simulation-based studies show that the proposed RAT selection mechanism results in lower number of Vertical Handovers (VHOs) and significant performance improvements in terms of packet delivery ratio, latency and application-level throughput.
Política editorial: https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Redes de ordenadores; Vehicular ad hoc networks; RAT; LTE